Answer:
Step-by-step explanation:
Let “a” be the first term and ”r” the common ratio of the GP. Then,
f(n) = ar^(n - 1).
f(2) + f(3) = 6f(4). (given)
ar + ar^2 = 6ar^3, or
1 + r = 6r^2, or
6r^2 - r - 1 = 0,
(3r + 1)(2r - 1) = 0.
r = -1/3, or 1/2.
If the common ratio is positive and the second term is 8 we have,
ar = 8, or
a*1/2 = 8, or a = 16.
f(n) = 16*(1/2)^(n - 1) = 2^4*2^(1 - n), or
f(n) = 2^(5 - n).
The first six terms of the GP are : 16, 8, 4, 2, 1, 1/2,…
××××××××××
Checking : f(2) + f(3) = 6f(4), (given).
LHS = 8 + 4 = 12.
RHS = 6* 2 = 12.
LHS = RHS.
Answer:
Given: The following system:
4x + y − 2z=18 ......[1]
2x-3y+3z = 21 ......[2]
x-3y=6 ......[3]
we can write equation [3] as;
3y = x-6 ......[4]
Multiply by 3 in equation [1] to both sides of an equation we get,
or
12x+3y-6z=54 ......[5]
Substituting the equation [4] in [2] and [5] we get;
2x-(x-6)+3z=21 or
2x-x+6+3z=21
Simplify:
x+3z=15 .....[6] [combine like terms]
12x+x-6-6z =54
Simplify:
13x-6z=60 ......[7] [Combine like terms]
On Solving equation [6] and [7] simultaneously,
x+3z=15
13x-6z=60
we get the value of x
i.e, x=6
Substitute the value of x in equation x+3z=15 we get
6+3z=15 or
3z=9
Simplify:
z=3
Also, substitute the value of x=6 in equation [3] we get the value of y;
x-3y=6
6-3y=6 or
-3y = 0
Simplify:
y = 0
Therefore, the solution to the system of three linear equation is, (6, 0 , 3)
Answer:
12 would be the distance between the two points
Step-by-step explanation:
True. The answer is the product of 4 and a number plus another number.